The Influence of Leadership in Building Intellectual Humility Among Employees: A Case Study of Mbarara Districtlocal Government - Desire Nabahinda (Uganda Christian University, 2026)
This study was guided by three objectives namely; to explore the manifestations of intellectual humility among employees, to explore the dominant leadership style in the organization, to explore the influence of leadership on intellectual humility. The study adopted a qualitative approach. Employees working at Mbarara District Local Government were eligible to participate in the study. 12 participants who were selected through a point of data saturation principle participated in the study. The findings described employees as open to learning from others especially in supportive departments. Only about half of respondents observed employees openly admitting to mistakes. In addition, other factors including; social environment, individual character emerged to be other factors that influence intellectual humility.
Undergraduate